2017
DOI: 10.1590/01047760201723012205
|View full text |Cite
|
Sign up to set email alerts
|

Hydrologic Impacts Due to the Changes in Riparian Buffer in a Headwater Watershed

Abstract: ABSTRACT:In recent years, concerns regarding the impacts of deforestation of riparian vegetation on water resources have created social and political tensions in Brazil. This research analyzed simulated hydrologic components of a 6.76 km 2 headwater watershed with different widths of riparian vegetation. Lavrinha Watershed (LW) hydrological responses were simulated using the Distributed Hydrology Soil Vegetation Model (DHSVM), which was forced using meteorological data from one station (2005)(2006)(2007)(2008)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 22 publications
2
10
0
2
Order By: Relevance
“…Our results indicate that a reduction or fragmentation of the RZ to the advantage of cropland expansion can increase soil bulk density and reduce its total and macro porosity. This could increase the overland flow generation, and it aligns with findings from Alvarenga et al (2017), who used the Distributed Hydrology Soil Vegetation Model (Sun et al, 2015) and found that an increase in the riparian width from 30 to 100 m decreased in 6.2% the total overland flow generation in a 6.76-km² catchment in the Atlantic rainforest.…”
Section: Implications Of Rz Conservation On Soil and Water Qualitysupporting
confidence: 86%
“…Our results indicate that a reduction or fragmentation of the RZ to the advantage of cropland expansion can increase soil bulk density and reduce its total and macro porosity. This could increase the overland flow generation, and it aligns with findings from Alvarenga et al (2017), who used the Distributed Hydrology Soil Vegetation Model (Sun et al, 2015) and found that an increase in the riparian width from 30 to 100 m decreased in 6.2% the total overland flow generation in a 6.76-km² catchment in the Atlantic rainforest.…”
Section: Implications Of Rz Conservation On Soil and Water Qualitysupporting
confidence: 86%
“…The Southeast region of Brazil is extremely relevant for the social and economic development of the country. The Grande River basin is located in southeastern Brazil and the Tropical Atlantic Forest in its headwater region (Mantiqueira Range), should be highlighted as one of the most important biodiversity hotspot of the world [1] [2]. In this basin, the annual variability of precipitation and temperature can be critical for human water consumption, irrigation, and hydropower generation [3] [4].…”
Section: Introductionmentioning
confidence: 99%
“…Due to spatial resolution limitation, polyline vector files have been used to outline both PPA and recovery areas, since we do not have geographic information to spatialize watercourses widths. Although unconventional, polyline vector files have been reported in literature as a suitable technique to simulate PPA limits (Alvarenga et al, 2017;Rosot et al, 2018;Rodríguez-Romero et al, 2018;Valera et al, 2019).…”
Section: Perspectives For Regularizationmentioning
confidence: 99%